2019
DOI: 10.1002/pc.25372
|View full text |Cite
|
Sign up to set email alerts
|

Erosive wear characteristics of E‐glass fiber reinforced silica fume and zinc oxide‐filled epoxy resin composites

Abstract: In the present study, the effect of addition of silica fume, also known as microsilica, and zinc oxide fillers on the erosive wear behavior of bidirectional E‐glass fiber‐based epoxy resin composites has been investigated. The amount of silica fume and zinc oxide fillers in the composites was changed in the interval from 0 to 16 wt.%. The erosive wear of the composites has been evaluated at different impingement angles from 20° to 90° and at four different impact velocities of 70, 100, 150, and 200 m/s. The er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…The impingement angle, impact velocity, and erodent size are the most studied factors that significantly influence erosion behavior. It was well documented in the literature that erosion wear remains highest for ductile and brittle materials at low (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and high (90 ) impingement angles, respectively. [27] In comparison, erosion wear is found to increase with an increase in impact velocity and erodent size.…”
Section: Taguchi Analysis For Erosion Wearmentioning
confidence: 91%
See 2 more Smart Citations
“…The impingement angle, impact velocity, and erodent size are the most studied factors that significantly influence erosion behavior. It was well documented in the literature that erosion wear remains highest for ductile and brittle materials at low (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and high (90 ) impingement angles, respectively. [27] In comparison, erosion wear is found to increase with an increase in impact velocity and erodent size.…”
Section: Taguchi Analysis For Erosion Wearmentioning
confidence: 91%
“…It was well documented in the literature that erosion wear remains highest for ductile and brittle materials at low (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and high (90 ) impingement angles, respectively. [27] In comparison, erosion wear is found to increase with an increase in impact velocity and erodent size. Therefore, in the current study, a combination of control factors for minimizing the erosion wear was optimized using the Taguchi approach.…”
Section: Taguchi Analysis For Erosion Wearmentioning
confidence: 91%
See 1 more Smart Citation
“…Several studies have been reported in the past for the investigation of erosive wear of polymer composite containing different types of fiber and fillers [ 37 ]. For instance, glass fiber reinforced polymer composite filled with micro silica and zinc oxide was fabricated via vacuum-assisted method and investigated for erosive wear behavior at a different impingent angle ranging from 20° to 90° [ 38 ]. It was reported that silica fumes enhanced the composite’s erosive wear resistance, while zinc oxide promoted erosive wear.…”
Section: Introductionmentioning
confidence: 99%
“…The strength of the material composites depends upon the atomic and molecular levels ranging at the nanoscale. The nanoscale particles for material ranges from 1 to 100nm, at the nano range the material possessed better features [5] . In organic metals and metal type oxide nano particles are utilized in many commercial uses as they have shown better for Electrical, Thermal, agentic, unique surface and optical features.…”
Section: Introductionmentioning
confidence: 99%